Nuclear distortions in the (p,2p) knockout reaction on 208Pb at an incident energy of 200 MeV. - Arendse, Gillian John (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.